Selection of indigenous lactic acid bacteria presenting anti-listerial activity, and their role in reducing the maturation period and assuring the safety of traditional Brazilian cheeses. (August 2018) - Campagnollo, Fernanda B.; Margalho, Larissa P.; Kamimura, Bruna A.; Feliciano, Marcelo D.; Freire, Luisa; Lopes, Letícia S.; Alvarenga, Verônica O.; Cadavez, Vasco A.P.; Gonzales-Barron, Ursula; Schaffner, Donald W.; Sant'Ana, Anderson S.
Abstract: Artisanal raw milk cheeses are highly appreciated dairy products in Brazil and ensuring their microbiological safety has been a great need. This study reports the isolation and characterization of lactic acid bacteria (LAB) strains with anti-listerial activity, and their effects on Listeria monocytogenes during refrigerated shelf-life of soft Minas cheese and ripening of semi-hard Minas cheese. LAB strains (n = 891) isolated from Minas artisanal cheeses (n = 244) were assessed for anti-listerial activity by deferred antagonism assay at 37 °C and 7 °C. The treatments comprised the production of soft or semi-hard Minas cheeses using raw or pasteurized milk, and including the addition of selected LAB only [ Lactobacillus brevis 2-392, Lactobacillus plantarum 1-399 and 4 Enterococcus faecalis (1-37, 2-49, 2-388 and 1-400)], L. monocytogenes only, selected LAB co-inoculated with L. monocytogenes, or without any added cultures. At 37 °C, 48.1% of LAB isolates showed anti-listerial capacity and 77.5% maintained activity at 7 °C. Selected LAB strains presented a bacteriostatic effect on L. monocytogenes in soft cheese. L. monocytogenes was inactivated during the ripening of semi-hard cheeses by the mix of LAB added. Times to attain a 4 log-reduction of L. monocytogenes were 15 and 21 days for semi-hard cheeses produced with raw and pasteurized milk, respectively. LAB with anti-listerial activity isolated from artisanal Minas cheeses can comprise an additional barrier to L. monocytogenes growth during the refrigerated storage of soft cheese and help shorten the ripening period of semi-hard cheeses aged at ambient temperature. Highlights: Listeria concentration fell 4-log in 15 days in raw semi-hard cheese w/added LAB. Listeria concentration fell 4-log in 21 days in pasteurized semi-hard cheese w/added LAB. More than 70% of LAB isolated on MRS agar showed Listeria antagonism at 37 °C. Added LAB significantly repressed but did not stop Listeria growth in soft cheese. Correspondence analysis showed significant differences in regional LAB strains.